Implementation of Smart Farming for Oyster Mushroom Cultivation Based on Wireless Sensor Network Using ESP8266 - Wahid, Abdul; Syahbani, Dimas; Adiba, Fhatiah (Internet of Things and Artificial Intelligence Journal, 2023)
Internet of Things (IoT) technology can facilitate daily work in various fields. This study aims to implement smart farming for oyster mushroom cultivation based on Wireless Sensor Network (WSN) and ESP8266. The sensors used are temperature and humidity sensors with NodeMCU ESP8266 as a microcontroller so that they can take advantage of the Internet of Things (IoT) concept. The design of the prototype tool is designed in the form of a prototype box. The prototype box has 2 rooms that aim to apply the Wireless Sensor Network (WSN) method, so that data in each different room can be retrieved and then sent the data to the website. Tests were carried out to measure the comparison of temperature and humidity sensors with manual measurement tools. The results of this study show an absolute error average of 0.606% for temperature data and an absolute error of 0.627% for humidity data. This shows that the overall system is good and responsive.